CRITICISM THROUGH MEMES FOR REPRESSIVE ACTIONS IN PPKM DARURAT IN WHATSAPP GROUPS - Sanjaya, Makroen; Febriani, Erna; Nurhayati, Kristina; Andrariladchi, Herdi (ASPIKOM Jabodetabek Region, 2022)
In the current era of new media, social criticism as a form of freedom of expression and speech is easier to facilitate. New media such as Whatsapp groups, provide various features, which allow criticism in the form of memes, to be produced, distributed and consumed by virtual communities who are members of Whatsapp groups. This article examines how criticisms of the government's repressive actions in the policy of Imposing Community Activity Restrictions (PPKM) Emergency/Level 4 and 3 Java-Bali through memes circulated in the new media platform Whatsapp group, why criticisms expressed through memes were carried out through the Whatsapp group, and what else types of memes as a form of social criticism circulating in Whatsapp groups. Pen ResultseThis research shows that the PPKM Emergency/Level 4 and 3 Java-Bali policies are repressive in nature, drawing a lot of criticism in the Whatsapp group in the form of memes. Memes, which literally mean ideas that spread quickly from person to person, are even more certain thanks to the new Whatsapp media which is interactive, has a diffuse (not centralized) character, avoids state control, and is democratic. State actors who are in charge of PPKM are generally the target of social criticism through memes in Whatsapp groups.